Association of brain gamma-tubulins with alpha beta-tubulin dimers - Sulimenko, Vadym; Sulimenko, Tetyana; Poznanovic, Slobodan; Nechiporuk-Zloy, Volodymyr; Böhm, Konrad J; Macurek, Libor; Unger, Eberhard; Dráber, Pavel (The Biochemical journal, 2002)
gamma-Tubulin is necessary for nucleation and polar orientation of microtubules in vivo. The molecular mechanism of microtubule nucleation by gamma-tubulin and the regulation of this process are not fully understood. Here we show that there are two gamma-tubulin forms in the brain that are present in complexes of various sizes. Large complexes tend to dissociate in the presence of a high salt concentration. Both gamma-tubulins co-polymerized with tubulin dimers, and multiple gamma-tubulin bands were identified in microtubule protein preparations under conditions of non-denaturing electrophoresis. Immunoprecipitation experiments with monoclonal antibodies against gamma-tubulin and alpha-tubulin revealed interactions of both gamma-tubulin forms with tubulin dimers, irrespective of the size of complexes. We suggest that, besides small and large gamma-tubulin complexes, other molecular gamma-tubulin form(s) exist in brain extracts. Two-dimensional electrophoresis revealed multiple charge variants of gamma-tubulin in both brain extracts and microtubule protein preparations. Post-translational modification(s) of gamma-tubulins might therefore have an important role in the regulation of microtubule nucleation in neuronal cells.
Keywords: dimerizace; Electrophoresis, Polyacrylamide Gel; Swine; protein - isoformy; tkáňové extrakty; Brain Chemistry; Protein Isoforms; frakcionace buněk; mozek - chemie; Animals; Dimerization; Tubulin; elektroforéza v polyakrylamidovém gelu; Tissue Extracts; Cell Fractionation; zvířata; prasata; tubulin